The role of [18F]FDG-PET/CT in gram-positive and gram-negative bacteraemia: A systematic review - Packham, Alice; Spence, Niamh; Bawa, Tanveer; Srinivasan, Rohit; Goodman, Anna L. (Frontiers in Nuclear Medicine, 2022)
Objectives Bacteraemia is associated with significant morbidity and mortality. [18F]FDG-PET/CT is increasingly used to detect infectious metastatic foci, however there remains international variation in its use. We performed a systematic review assessing the impact of [18F]FDG-PET/CT in adult inpatients with gram-positive and Gram-negative bacteraemia. Design The systematic review was performed according to PRISMA guidelines. Studies published between 2009 and December 2021 were searched in MEDLINE, EMBASE and Cochrane clinical trials database. Data extraction and quality assessment was performed using ROBINS-I and GRADE. Setting Eligible study designs included randomised-controlled trials, clinically-controlled trials, prospective trials, retrospective trials, case-control studies, and non-controlled studies. Participants Studies solely assessing adult inpatients with blood-culture confirmed bacteraemia with one cohort of patients receiving [18F]FDG-PET/CT were included. Main outcome measures primary outcomes were mortality, identification of metastatic foci and relapse rate. Studies not examining any of the pre-specified outcomes were excluded. Results Ten studies were included, of which five had a non-PET/CT control arm. Overall, there was low quality of evidence that [18F]FDG-PET/CT is associated with reduced mortality, improved identification of metastatic foci and reduced relapse rate. Six studies assessed Staphylococcus aureus bacteraemia (SAB) only; nine studies included Gram-positive bacteraemia only, and one study included data from Gram-negative bacteraemia. Two studies compared outcomes between patients with different types of bacteraemia. Four studies identified a statistically significant difference in mortality in [18F]FDG-PET/CT recipients and controls. Relapse rate was significantly reduced in patients with SAB who received [18F]FDG-PET/CT. Studies identified significantly higher detection of metastatic foci in [18F]FDG-PET/CT recipients compared to controls. [18F]FDG-PET/CT was the first to identify an infectious site in 35.5% to 67.2% of overall foci identified. Conclusions Further research is required to establish the role of [18F]FDG-PET/CT in bacteraemia, and its impact on management and mortality.